A Educação bilíngue na escola Karajá de Buridina e as influências dos sistemas tecnológicos de informação e comunicação - Souza, Gisele Luiza de (2018)
This research deals with the presence of Information and Communication Technologies (ICTs) and their influence over the Portuguese bilingual education / indigenous mother tongue of children and adolescents belonging to the Karajám ethnic group enrolled in the Maurehi Indian State School, located in Buridina Village, urban area of the city of Aruanã, State of Goiás. Based on the reflection of the conceptions of bilingualism and of the linguistic policies developed in the indigenous context, we describe the current sociolinguistic reality of the village, the community / school relationship and how the students' contact with ICT has reflected in their lives, culture and language. For this, the research was theoretically based on the historical-social and linguistic trajectory of the Karajá people of Buridina (PIMENTEL DA SILVA, 2004, 2008, among others; bilingualism and the different bilingual typologies (GROSJEAN, 1982, 2013, BUTLER and HAKUTA, 2006, GASS and SELINKER, 2008); in a research that deals with the linguistic and educational policies developed in the indigenous context (HAMEL, 1988, 1993; FLEURI, 2006; OLIVEIRA, 2004, 2007; CALVET, 2007); in studies on multiculturalism, interculturality and indigenous school education (GRUPIONI, 2001, MOREIRA and CANDAU, 2010, LÓPEZ, 2013), and finally on works that discuss the relationship of indigenous communities with cyberspace and the inclusion of indigenous peoples and languages in the digital world (CASTELLS, 1999; NUNES JUNIOR, 2009; D'ANGELIS, 2010; RENESSE, 2011; GOMES, 2016). As a research that prioritizes the interaction of the researcher with the participants, we chose to adopt an ethnographic study (ANDRÉ, 1995; GEERTZ, 2015), which was constructed from a trans-meteorological perspective (MALDONADO, 2002, 2008; AGUIAR, 2011) as the main methodology, combines mixed methodological proposals that allows a more comprehensive epistemic view of the object. In this regard, the observations, the field diary and the interviews analyzed from a qualitative approach (LÜDKE and ANDRÉ, 1986; MOREIRA and CALEFFE, 2008) are highlighted as instruments for the construction of this study. The results suggest that the use of ICTs among students of Buridina, especially through the use of cellular devices and computers with access to broadband internet, has intensified the frequency of contact and use of the Portuguese language in the village and, consequently, dominance of the use of the Portuguese mainly among the younger generations of the community that demonstrate greater distance from the Karajá mother tongue, Iny Rubè.